1999
DOI: 10.1111/j.1600-0404.1999.tb00674.x
|View full text |Cite
|
Sign up to set email alerts
|

Late epileptic seizures after cerebral infarction

Abstract: Simple partial, and mainly motor seizures, with or without secondary generalization, accounted for 80% of the classifiable seizures but it was not possible to determine the seizure type in half of the cases. Factors that appeared to be predictive of seizure development were the presence of large cortical infarcts and the presence of apparently preserved cerebral tissue within the infarcted area. Seizures were rare in patients with lacunar infarction but the presence of associated leukoaraiosis increased the ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
46
1
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 22 publications
6
46
1
2
Order By: Relevance
“…A poststroke seizure is more common with ICH 189 or when the stroke involves cerebral cortex 190 ; seizures in patients with lacunar stroke are rare. 191 Estimates of the percentage of patients having a seizure during the first few days after a stroke range from 2% to 23% in various studies, with the true risk toward the lower end of this range. 191,192 A minority of such patients will have a recurrent seizure, and status epilepticus is uncommon.…”
Section: Seizure Prophylaxismentioning
confidence: 99%
See 1 more Smart Citation
“…A poststroke seizure is more common with ICH 189 or when the stroke involves cerebral cortex 190 ; seizures in patients with lacunar stroke are rare. 191 Estimates of the percentage of patients having a seizure during the first few days after a stroke range from 2% to 23% in various studies, with the true risk toward the lower end of this range. 191,192 A minority of such patients will have a recurrent seizure, and status epilepticus is uncommon.…”
Section: Seizure Prophylaxismentioning
confidence: 99%
“…191 Estimates of the percentage of patients having a seizure during the first few days after a stroke range from 2% to 23% in various studies, with the true risk toward the lower end of this range. 191,192 A minority of such patients will have a recurrent seizure, and status epilepticus is uncommon. 193 Estimates for the incidence of a seizure developing late after stroke are even more variable, ranging from 3% to 67%.…”
Section: Seizure Prophylaxismentioning
confidence: 99%
“…Late seizures vary from 3% to 67%. 735, 736 The risk of late seizures is higher in patients with preexisting dementia. 737 Status epilepticus is uncommon.…”
Section: Seizuresmentioning
confidence: 99%
“…1003 A great variance is also reported in the incidence of recurrent and late-onset seizures. 1004,1005 With few data available on the efficacy of anticonvulsants in the treatment of seizures in stroke patients, current recommendations are based on the established management of seizures that may complicate any neurological illness. No studies to date have demonstrated a benefit of prophylactic anticonvulsant use after ischemic stroke, and little information exists on indications for the long-term use of anticonvulsants after a seizure.…”
Section: Seizuresmentioning
confidence: 99%